Effect of heat treatment with antioxidants on oxygen radical scavenging during storage of zucchini squash - Прісс, Олеся Петрівна; Калитка, Валентина Василівна (Eastern-European Journal of Enterprise Technologies, 2015)
Despite the proven effectiveness of heat treatment and antioxidants for reducing oxidative chilling injury, their combined effect during storage of zucchini squash was not considered in this aspect. The paper describes the results of investigating the effect of heat treatment with the antioxidant composition on the chilling injury level, the amount of malonic dialdehyde and dynamics of enzymatic antioxidants during storage of zucchini squash. It was found that application of heat treatment with antioxidants reduces the chilling injury during storage of zucchini squash. The combination of heat treatment and antioxidants allows to reduce or stabilize the amount of malonic dialdehyde at the same level, depending on the chilling sensitivity of the zucchini squash hybrid. Heat treatment with antioxidants induces the activity of superoxide dismutase and catalase in the beginning of storage. The superoxide dismutase activity stabilizes until the 18th day of storage at the same level, and catalase activity reduction slows down by 30...40% depending on the zucchini squash hybrid. Using heat treatment with antioxidants reduces the growth rate of peroxidase activity compared to control samples by 7...18%. Close inverse correlations between the level of malonic dialdehyde, the activity of superoxide dismutase and catalase indicate the strengthening of the antioxidant function of these enzymes in experimental groups of fruits. The combination of heat treatment and antioxidants to prepare zucchini squash for storage allows to effectively reduce oxidative chilling injury.